Planning environmental education to raise awareness of climate perception and thermal comfort among pedestrians on Avenida Frei Serafim, downtown Teresina (Research, Society and Development, 2022)
The city of Teresina, capital of Piauí, is popularly seen as one of the hottest capitals in Brazil, with an average temperature of 28°C and maximum temperatures that exceed 40°C. High temperatures are the reason for campaigns to encourage the prevention of damage to health caused by these climatic fluctuations that increase, for example, the risk of skin problems. However, in addition to health problems arising from an uncomfortable environment, with a temperature that tends to be unhealthy; It is interesting to survey data on climate perception among different audiences in the capital of Piauí, as an experimental means of obtaining information to help in the formatting of public policies for the different managing bodies, as well as to think about environmental education actions. The present work was developed with the purpose of analyzing how the perception of thermal discomfort occurs from the perspective of the pedestrian, (in addition to other climatic factors) that characterize the high temperatures experienced by Teresina society in large periods of the year, from of a sample based on Av. Friar Seraphim; where we sought to individually assess the heightened perception of heat; both by climatic phenomena and by human activity identified in the area, directly influencing the quality of life of people who transit there, as well as; based on the principle that the actions to be carried out by the public power must be thought of jointly with society, enabling its integration and participation in decision-making that interfere in public spaces.